2008
DOI: 10.1177/117718010800400112
|View full text |Cite
|
Sign up to set email alerts
|

Saili Mo Le Lumana'i: Research on Samoan Students’ Learning Perspectives and the Impact on their Achievement

Abstract: This paper discusses the findings of a collaborative research project between the National University of Samoa (NUS) and Unitec New Zealand, which examined the concept of 'Samoan pedagogy' and the learning processes of Samoan students. The study is based on the experiences of 24 Samoan students (Samoan and New Zealand born) who had been studying for education qualifications. It concludes that Samoan students learn in a variety of diverse ways, and that there are no differences between Island born and New Zeala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 8 publications
4
26
0
Order By: Relevance
“…Discussions and interviews with participants indicated that they needed further demonstration and assistance with understanding texts, essay writing, and language analysis. Similar to a previous study of Samoan student learning experiences in Samoa and New Zealand (Utumapu-McBride et al 2008), participants from the Melbourne Homework Study Groups preferred practical activities and demonstrations of how to write for an audience. In designing the approach to undertaking research with participants, Pacific methodology was used to formulate pedagogy that enhanced learning and understanding with participants.…”
Section: Strengthsbased Pedagogymentioning
confidence: 91%
“…Discussions and interviews with participants indicated that they needed further demonstration and assistance with understanding texts, essay writing, and language analysis. Similar to a previous study of Samoan student learning experiences in Samoa and New Zealand (Utumapu-McBride et al 2008), participants from the Melbourne Homework Study Groups preferred practical activities and demonstrations of how to write for an audience. In designing the approach to undertaking research with participants, Pacific methodology was used to formulate pedagogy that enhanced learning and understanding with participants.…”
Section: Strengthsbased Pedagogymentioning
confidence: 91%
“…Utumapu- McBride et al (2008) urges the education system, on its ability to nurture and help students so they can succeed regardless of the system. Those who did do well had access to good teachers, relevant resources, supportive environment and language was not a barrier.…”
Section: Sāmoan Students In Higher Education In Aotearoa New Zealandmentioning
confidence: 99%
“…Revisiting Utumapu-McBride et al (2008) and Tuia ( 2108) their studies focused on NUS students from the Faculty of Education. A key finding was the critique of the lecturers which was a prominent voice from the students.…”
Section: Samoan Students In Higher Education In Samoamentioning
confidence: 99%
See 2 more Smart Citations